1980
DOI: 10.1002/art.1780231109
|View full text |Cite
|
Sign up to set email alerts
|

The C1q binding assay in systemic lupus erythematosus

Abstract: To investigate the relationship of Clq binding assay (ClqBA) to disease activity in systemic lupus erythematosus (SLE), a retrospective study was carried out on 232 ClqBA performed in 33 patients with SLE.When initial values only were assessed (33 tests in 33 patients), there was no relationship between positive and negative ClqBA and abnormal renal function (P = 0.482, Fisher exact test). Of 87 tests performed during active renal disease, 34 (39%) were positive; of 48 tests during active non-renal disease, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 23 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…We were not surprised by the lack of relationship between measures of serum complement and staphylococcal protein A immune complex binding, since this also has been noted by other investigators (9,11,42).…”
Section: Discussionsupporting
confidence: 79%
“…We were not surprised by the lack of relationship between measures of serum complement and staphylococcal protein A immune complex binding, since this also has been noted by other investigators (9,11,42).…”
Section: Discussionsupporting
confidence: 79%
“…Several studies have shown that by comparing groups of patients with active disease with groups of patients with inactive disease, significant correlations between various laboratory parameters and disease activity can be found (16)(17)(18)29,30). Our study confirmed this.…”
Section: Discussionmentioning
confidence: 99%
“…Yet despite their presence, it remains difficult to determine precisely the pathogenetic potential of immune complexes in systemic vasculitis since they are rarely detectable in 100% of these patients (Pussell et al, 1978), they may be present in otherwise normal tissues (Baart de la Faille-Kuyper et al, 1973) or, conversely, undetectable in tissues with typical vasculitic lesions (Conn et al, 1972), and disease activity may not correlate with measured levels (Inman et al, 1980). Problems in interpretation also arise since levels of immune complexes measured by different methods correlate poorly (Lambert et al, 1978).…”
Section: Immuno-pathogenetic Mechanisms Immune Complexes (A) Animal Mmentioning
confidence: 99%